Cambridge IELTS 14: General training with answers - Cambridge IELTS (Sonipat; Kundli Cambridge University Press; Rajkamal Electric Press, 2021)
Authentic examination papers from Cambridge Assessment English provide perfect practice because they are EXACTLY like the real test.Inside IELTS 14 General Training with Answers with Audio learners find FOUR complete examination papers plus details of the different parts of the test and the scoring system, so as to allow familiarisation with the test format and practise in exam techniques. This book comes with answers, audio scripts, sample writing answers and audio. Use the access code on the inside front cover to download all the material for the Listening tests.
Keywords: English Grammar